Advancements in CRISPR-Based Therapies for Genetic Modulation in Neurodegenerative Disorders - Bhushan, Bharat; Singh, Kuldeep; Kumar, Shivendra; Bhardwaj, Anjali (Current Gene Therapy, 2025)
Neurodegenerative disorders pose significant challenges in the realm of healthcare, as these conditions manifest in complex, multifaceted ways, often attributed to genetic anomalies. With the emergence of CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) technology, a new frontier has been unveiled in the quest for targeted, precise genetic manipulation. This abstract explores the recent advancements and potential applications of CRISPR-based therapies in addressing genetic components contributing to various neurodegenerative disorders. The review delves into the foundational principles of CRISPR technology, highlighting its unparalleled ability to edit genetic sequences with unprecedented precision. In addition, it talks about the latest progress in using CRISPR to target specific genetic mutations linked to neurodegenerative diseases like Huntington's disease, Alzheimer's disease, amyotrophic lateral sclerosis (ALS), and Parkinson's disease. It talks about the most important studies and trials that show how well and safely CRISPR-based therapies work. This shows how this technology can change genetic variants that cause diseases. Notably, the discussion emphasizes the challenges and ethical considerations associated with the implementation of CRISPR in clinical settings, including off-target effects, delivery methods, and long-term implications. Furthermore, the article explores the prospects and potential hurdles in the widespread application of CRISPR technology for treating neurodegenerative disorders. It touches upon the need for continued research, improved delivery mechanisms, and ethical frameworks to ensure responsible and equitable access to these groundbreaking therapies.
Keywords: gene editing